1997
DOI: 10.1111/1540-6229.00713
|View full text |Cite
|
Sign up to set email alerts
|

Currency Swaps and International Real Estate Investment

Abstract: This paper examines the efficacy of currency swaps as a hedging mechanism for the exchange rate risk associated with foreign investment in real estate. Earlier studies have concentrated on short-term hedging instruments such as options and forward contracts. Currency swaps are better suited for use on investments with long-term holding periods such as real estate. The findings indicate that, although hedging United States real estate investments with currency swaps suppresses most of the risk induced by curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 15 publications
1
25
0
1
Order By: Relevance
“…Based on this survey, Cross currency swaps were the most frequently used capital hedging strategy vehicles; eg: Babcock & Brown Japan, Macquarie CountryWide, Macquarie DDR, Macquarie Office, Macquarie ProLogis; confirming previous research on the most effective capital risk management strategy (Johnson et al, 1998;Ziobrowski et al, 1997). Specific cross currency swaps implemented for capital hedging (Macquarie Research, 2006) include:…”
Section: Capital Risk Managementsupporting
confidence: 75%
See 2 more Smart Citations
“…Based on this survey, Cross currency swaps were the most frequently used capital hedging strategy vehicles; eg: Babcock & Brown Japan, Macquarie CountryWide, Macquarie DDR, Macquarie Office, Macquarie ProLogis; confirming previous research on the most effective capital risk management strategy (Johnson et al, 1998;Ziobrowski et al, 1997). Specific cross currency swaps implemented for capital hedging (Macquarie Research, 2006) include:…”
Section: Capital Risk Managementsupporting
confidence: 75%
“…The appropriateness of specific currency hedging techniques has also been assessed, including forward contracts (eg: Ziobrowski and Ziobrowski, 1995), currency options (eg: Ziobrowski and Ziobrowski, 1993) and currency swaps (eg: Johnson et al, 1998;Ziobrowski et al, 1997). Other currency risk management strategies available Mills, 2004, 2006;Newell and Worzala, 1995) are to increase gearing and borrow in local currency as a natural hedge, use local cashflow for interest payments, reinvest in same country, and diversify via establishing a global property portfolio.…”
Section: Currency Risk Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…(for example Ziobrowski & Curcio 1991, Ziobrowski & Ziobrowski 1993, Ziobrowski et al 1997. In fact, very few papers have considered the role that international real estate can play in a portfolio context.…”
mentioning
confidence: 99%
“…Ziobrowski et al (1997) demonstrated how currency risk remains a significant investment influence, even over extended time periods, where trends should theoretically reach equilibrium. This is supported by the 'Exchange-RateDisconnect-Puzzle', which implies a disconnection between economic elements and exchange rates (Cheung et al, 2005;Mark, 1995).…”
Section: Risks In International Real Estate Investmentsmentioning
confidence: 99%